The impacts of advanced digital technologies on workplaces and workforce - LUANGSOMBATH , Soulichanh; NOUTHAPHONE, Thiphachanh; PHALYCHAN, Bounmy; VINNALATH4, Khounmy; SYSAVATH5, Somphane; VINNALATH6, Khounmy; PHENGSOM7 , Manivone; PHOMPHITHAK8, Chansy (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Advanced digital technology is influential in working areas because of the efficiency to deliver working performance and gain more outputs. Technology is pervasive in aspects of works. It requires employees to have the knowledge and the ability to apply it to facilitate their tasks. This study aims to explore the impacts of advanced digital technology in the workforce and workplaces. The location site of research is the education department of Naxaythong district. The sampling group comprises 30 who have worked related to technology. The survey applied a questionnaire to collect the data. Questions are designed on Google form to facilitate data collection. For data analysis, researchers deployed a computer program as SPSS to analyze the data. The study found that digital technology knowledge is essential in the workforce because it empowers working performance. The workforce requires the ability to utilize technology to increase work output. It can decrease the number of time employees spends on repetitive tasks. Nevertheless, the unskilled workforce tends to lose their job opportunity to get a job and promotion when they lack knowledge of digital technology.